EFFECTS OF THE MASS TRANSFER AND PRESENCE OF THE THIRD COMPONENTS IN CLOSE BINARY STELLAR SYSTEMS - Tvardovskyi, D. E.; Marsakova, V. I.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
In our research, we have studied 6 close binary stellar systems which are eclipsing variables of β Lyrae and W Ursae Majoris types of variability. We have studied their O-C curves. To build them, we used moments of minima, listed in the BRNO database. Also, we used ones, which we obtained as the result of processing of observational data taken from AAVSO database. As the result of the O-C analysis, we detected that all of these stars have parabolic O-C curves, which might be caused by mass transfer from one component to another. In an addition, 3 from researched stars (U Peg,V0523 Cas and WZ Cyg) have superimposed parabolic and cyclic O-C changes that could be caused by presence of the third components in the systems. Also, we calculated minimal possible masses of third components, rates of the mass transfer for these systems and corrected the ephemerides.